Developments in Nitrosocarbonyl Chemistry: Mild Oxidation of N-Substituted Hydroxylamines Leads to New Discoveries - Palmer, Leoni I.; Frazier, Charles P.; Read de Alaniz, Javier (Synthesis, 2014)
This account describes the discovery and development of mild and efficient protocols for the generation of highly reactive nitroso compounds to allow their subsequent use in previously inaccessible or challenging chemistries.1 Introduction2 Formation of Nitrosocarbonyl Compounds3 The Nitrosocarbonyl Ene Reaction3.1 Single-Pot Nitrosocarbonyl Ene Reactions3.2 Copper-Catalyzed Aerobic Oxidation for the Nitrosocarbonyl Ene Reaction4 The Hetero-Diels–Alder Reaction as a Platform for Studying Aerobic Oxidation5 Dual Catalysis and α-Functionalization Reactions5.1 α-Amination Reaction of β-Keto Esters5.2 α-Oxygenation Reaction of β-Keto Esters6 The Future of Nitroso Chemistry
Keywords: aerobic oxidation; nitroso; α-functionalization; electrophilic synthon; hydroxylamines